2014
DOI: 10.3389/fmicb.2014.00059
|View full text |Cite
|
Sign up to set email alerts
|

Imaging DivIVA dynamics using photo-convertible and activatable fluorophores in Bacillus subtilis

Abstract: Most rod-shape model organisms such as Escherichia coli or Bacillus subtilis utilize two inhibitory systems for correct positioning of the cell division apparatus. While the nucleoid occlusion system acts in vicinity of the nucleoid, the Min system was thought to protect the cell poles from futile division leading to DNA-free miniature cells. The Min system is composed of an inhibitory protein, MinC, which acts at the level of the FtsZ ring formation. MinC is recruited to the membrane by MinD, a member of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…It may, for example, involve the selective degradation of DivIVA on the mother cell face of the polar septum or may involve a transfer of pole-localized DivIVA molecules to the forespore-proximal side of the polar septum which we were unable to measure using our current experimental setup. Such a transfer has indeed been recently reported for vegetative septa, which may occur in 5–20 mins [79]. Curiously, the presence of Min proteins, which are typically recruited by DivIVA, on the forespore-proximal face of the polar septum has been implicated in maintaining the polarity of DNA translocation [80].…”
Section: Discussionmentioning
confidence: 54%
“…It may, for example, involve the selective degradation of DivIVA on the mother cell face of the polar septum or may involve a transfer of pole-localized DivIVA molecules to the forespore-proximal side of the polar septum which we were unable to measure using our current experimental setup. Such a transfer has indeed been recently reported for vegetative septa, which may occur in 5–20 mins [79]. Curiously, the presence of Min proteins, which are typically recruited by DivIVA, on the forespore-proximal face of the polar septum has been implicated in maintaining the polarity of DNA translocation [80].…”
Section: Discussionmentioning
confidence: 54%
“…DivIVA has previously been reported as static [75], however those FRAP experiments were carried out using overexpression strains and a much shorter timeframe than here. Earlier observation from our own lab using a merodiploid strain already suggested that DivIVA is dynamic [62]. Roughly, two thirds of DivIVA molecules were participating in dynamics.…”
Section: Resultsmentioning
confidence: 98%
“…Since this did not meet the set standards for this study, we turned towards strain 1803 [74], carrying a divIVA-GFP copy with its native promoter in the ectopic amyE locus. While DivIVA-GFP has been shown to not fully complement a ΔdivIVA strain [74, 75], it still localizes correctly and can be used for studies of DivIVA dynamics [62, 75]. Additionally, we performed FRAP on DivIVA-mNeonGreen, which only shows a mild phenotype ( Tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples of positive curvature sensing proteins include septins and BAR (Bin/amphiphysin/Rvs) domain proteins in eukaryotes and SpoVM in sporulating bacteria (Cannon et al, 2017). In gram positive bacteria, DivIVA recognizes negative, concave membrane curvature, and self-assembles at the cytoplasmic side of the pole and curved region of the cell division septum to form a structural scaffold (Edwards and Errington, 1997;Letek et al, 2008;Lenarcic et al, 2009;Ramamurthi and Losick, 2009;Kaval and Halbedel, 2012;Bach et al, 2014). DivIVA, which is a filamentous, coiled-coil protein, aids in the localizations of various target proteins at the pole for cell-wall growth and a variety of biological functions (Rudner and Losick, 2010;Laloux and Jacobs-Wagner, 2014;Halbedel and Lewis, 2019;Hammond et al, 2019).…”
Section: Introductionmentioning
confidence: 99%